2011
DOI: 10.1007/s11238-011-9250-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward uncertainty among the poor: an experiment in rural Ethiopia

Abstract: We investigate risk and ambiguity attitudes among Ethiopian farmers in one of the poorest regions of the world. Strong risk aversion and ambiguity aversion were found with the Ethiopian farmers. We compared their attitudes to those of a Western university student sample elicited by the same decision task. Ambiguity aversion was similar for farmers and students, but farmers were more risk averse. Our results show that ambiguity aversion is not restricted to Western student populations, and that studies of agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 46 publications
3
36
2
Order By: Relevance
“…Some papers report a positive correlation between subjects' aversion against risk and their ambiguity aversion (Abdellaoui et al 2011, Dimmock et al 2012 Weitzel 2011), but others do not find a significant correlation or even a negative one (Cohen et al 2011, Akay et al 2012, Cubitt et al 2012, Sutter et al 2013. Again, a possible explanation for the different findings is the way in which the attitudes towards risk and ambiguity are measured.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers report a positive correlation between subjects' aversion against risk and their ambiguity aversion (Abdellaoui et al 2011, Dimmock et al 2012 Weitzel 2011), but others do not find a significant correlation or even a negative one (Cohen et al 2011, Akay et al 2012, Cubitt et al 2012, Sutter et al 2013. Again, a possible explanation for the different findings is the way in which the attitudes towards risk and ambiguity are measured.…”
Section: Introductionmentioning
confidence: 99%
“…And ambiguity aversion has predictive power for real life decisions (Ross et al 2012;Engle-Warnick et al 2011;Sutter et al 2013;Bianchi and Tallon 2014;Dimmock et al 2016a, b). However, the literature on the relationship between risk aversion and income 1 is much richer than the literature on the relationship between ambiguity aversion and income (Akay et al 2012;Butler et al 2014;Dimmock et al 2016b). The main reason for this gap in the literature is that until recently no tools were available to measure ambiguity attitudes in natural circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the developing world found no relationship between wealth and ambiguity aversion (Engle-Warnick et al 2011;Akay et al 2012;Cardenas and Carpenter 2013). These studies included proxies for wealth as control variables where the main research questions concerned the relationship between people's ambiguity attitudes and some real life decisions such as adoption of new technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the focus of research efforts to establish the determinants of technology adoption has shifted away from market imperfections and market constraints to the role played by information, education, and social relationships (Akay et al, 2009). For example, a review of 21 studies on the adoption of improved maize varieties in developing countries showed that socio-economic factors such age, education, farming experience, and gender were some of the determinant of attitudinal change among farmers (Kafle, 2010).…”
Section: Research Questions and Propositionsmentioning
confidence: 99%